Formation of educational level of the population of ukraine in the conditions of formation of information society - Martynovych, Nataliia Oleksandrivna; Boichenko, Elina Borysivna; Vivchar, Oksana; Myskova, Nataliia; Popovych, Oksana; Kasianenko, Oksana (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The scientific Foundation of the formation of the educational level of the population of Ukraine in the conditions of the creation of the information society was early research. The study based on one of the strategic goals of sustainable development, namely: "Overcoming poverty in all its forms. The current provisions of the implementation of sustainable development were approved in 2015 at the UN Summit on sustainable development. Improving the educational level of the population of Ukraine in the conditions of formation of the information society is the basis of the mechanism of poverty prevention and improving the quality of life. In the article, the authors established the essence of the concept of "information society", determined the prerequisites for the emergence of the information society in Ukraine, revealed the peculiarity of the formation of the information society in Ukraine. The authors proposed an author's vision of the process of creation of the educational level of the population, substantiated the feasibility of applying a systematic approach to diagnosing the level of education of the people. The authors examined the results of diagnosing the educational level of the population of Ukraine in the context of the formation of the information society for the period 2000-2018.

Науковою основою формування освітнього рівня населення України в умовах створення інформаційного суспільства стали ранні дослідження. Дослідження базується на одній зі стратегічних цілей сталого розвитку, а саме: «Подолання бідності в усіх її формах». Чинні положення щодо реалізації сталого розвитку були схвалені у 2015 році на Саміті ООН зі сталого розвитку. Підвищення освітнього рівня населення України в умовах формування інформаційного суспільства є основою механізму запобігання бідності та покращення якості життя. У статті автори встановили сутність поняття «інформаційне суспільство», визначили передумови виникнення інформаційного суспільства в Україні, розкрили особливості формування інформаційного суспільства в Україні. Вчені запропонували авторське бачення процесу створення освітнього рівня населення, обґрунтували доцільність застосування системного підходу до діагностики рівня освіти народу. Припущення довели шляхом діагностики освітнього рівня населення України в контексті формування інформаційного суспільства за період 2000-2018 років.
Keywords: educational level; information society; population; Ukraine; рівень освіти; інформаційне суспільство; населення; Україна